Deteksi Tingkat Kesegaran Daging Ayam Menggunakan K-Nearest Neighbor - Irfan Purwanto; M. Afriansyah; Kusrini Kusrini (CCIT Journal, 2019)
The high demand for meat and the limited availability of meat on the market, make the price of meat become expensive and more and more traders are mixing rotten meat into fresh meat. To avoid risk, the public as consumers must be aware and know the characteristics of rotten meat and the difference with fresh meat. This study developed a fresh meat detection device using the TCS-230 RGB color sensor. The tool works by measuring the composition of RGB colors in identified meat and comparing with the reference composition of fresh meat RGB color. K-Neirest Neighbor as a method for introducing the freshness of chicken meat tested. The input used in the K-Neirest Neighbor is in the form of RGB color values ​​obtained from the color sensor.In this study, meat freshness was tested using TCS-230 color sensor with an accuracy rate of 87% with a positive precision of 92% and negative precision of 67%